Polymeric chains, hydrogen bonds and magnetism in Nd(III) adipates - Echeverría, Gustavo Alberto (2004)
An AC susceptibility study of [Nd2(O2C(CH 2)4CO2)3(H2O) 2] (1) obtained from a solution at ambient conditions was performed in the range 14-320 K. An ordering transition, TC = 280(2) K, not related to a structural phase transition, a ferromagnetic like Curie-Weiss behavior above TC, an antiferromagnetic like dependence of χ′-1 at the lowest temperatures and a non-linear thermal dependence of χ′-1 in the in-between region have been observed. Samples prepared by hydration of 1 during different periods showed enhancement of the observed features. Links between water content, crystal structure and magnetic response are discussed. © 2004 Elsevier B.V. All rights reserved.